Pengembangan LKPD dengan Pendekatan Saintifik Berbasis Etnomatematika Permainan Tradisional Cak-Belikak pada Materi Geometri Segi Banyak di Kelas IV Sekolah Dasar - Nurochim; Agus Susanta; Irwan Koto (UNIB Press, 2023)
The purpose of this study was to develop worksheets with a scientific approach based on the ethnomathematics of the traditional Cak-Belikak game on polygon geometry material in grade IV elementary schools that are valid and interesting for students. The LKPD development model used is the 4D model from Thiagarajan, which consists of the following stages: 1) Define, 2) Design, 3) Develop, and 4) Disseminate. Development activities are limited to the development stage (Develop). The dissemination stage was not carried out due to the Covid-19 pandemic situation. The results of the analysis of the validity of LKPD using the Aiken's V formula show that the results of the development of LKPD in this study,